Pessimism from the scientific worldview: examining a critique of Islam - Hasan, Md Maruf; Ali, Mohd Mumtaz (International Journal of Research in Engineering, Science and Management, 2024)
Islamophobia is on the rise across the world. The alarming issue, however, is Islamophobic attitudes are noticed among Muslim youths within Muslim societies. One of the root causes to develop pessimistic attitudes towards world religions is scientific worldview. In the past, scientific worldview was a threat to Christian world of West. Recently, the trend seems to enter within Muslim lands. Some Muslim youths are vulnerable to the scientific worldview, especially youths who are lacking in Islamic education. This paper uses qualitative methodology. Library research has been adopted to understand the trend of pessimism deriving from the scientific worldview. The research finds that the deception of knowledge, e.g. Scientific Worldview, is not a new phenomenon rather this sort of phenomenon existed during medieval Islamic period among some Muslim intellectuals due to the influence of Greek philosophy. This study also suggests the possible Quranic remedy for Muslim youths to encounter pessimism of scientific worldview.